Management Accountants' Business Orientation and Involvement in Incentive Compensation Empirical Results from a Cross-Sectional Survey - Wolf, Sebastian (Controlling & Business Accounting, 2018)
Changing roles of management accountants have been intensively discussed in business practice and academic research. The objective of this empirical study is to gain a deeper understanding of management accountants' business orientation and extended tasks. Based on data collected from the top 1,500 companies in Germany, results reveal that especially subjective norms have a strong impact on the practice of management accountants acting business-oriented. Furthermore, the results reinforce the frequently postulated positive effect of management accountants' business orientation. The analyses also show positive associations between the involvement of management accountants in incentive compensation, the effort effects of incentive schemes, and firm performance.